Avaliação da qualidade das águas superficiais da sub-bacia do rio Capivari no município de Chapada do Norte – MG / Evaluation of the quality of surface waters of the Capivari river sub-basin in the municipality of Chapada do Norte - MG - Ferreira Costa, Paulo Sergio (Caderno de Geografia, 2016)
A água é um dos recursos naturais mais preciosos e é indispensável à manutenção da vida. Conhecer a quantidade e a qualidade dos recursos hídricos do país é pressuposto para definição de estratégias que busquem a sua conservação, recuperação e o seu uso racional é meta imprescindível para toda a sociedade. Sabe-se que a ocupação e o uso do solo alteram os processos físicos, químicos e biológicos dos recursos hídricos. Não obstante ser o país mais bem aquinhoado em termos percentuais de água doce, sua distribuição geográfica é bastante irregular no Brasil. Regiões como o semiárido nordestino e o Vale do Jequitinhonha mineiro, historicamente enfrentam problemas relacionados à falta d’água. Nos últimos anos essa situação tem piorado, em termos de quantidade e qualidade. Assim, a proposta deste trabalho consiste na avaliação da qualidade das águas superficiais da sub-bacia do rio Capivari no município de Chapada do Norte, Alto Jequitinhonha, nordeste de Minas Gerais. Foi utilizado como técnica de análise o Índice de Qualidade da Água – IQA, utilizado pelos principais órgãos de gestão das águas do país, como a CETESB/SP e o IGAM/MG. Palavras-Chave: Sub-bacia do rio Capivari; Chapada do Norte; IQA. Abstract Water is one of the most precious natural resources and is indispensable to the maintenance of life. Knowing the quantity and quality of water resources of the country is a precondition for developing strategies that seek their conservation, recovery and rational use and indispensable goal for the whole society. It is known that the occupation and land use modify the physical, chemical and biological water resources. Despite being the country's most well apportioned in freshwater percentage terms, their geographical distribution is quite irregular in Brazil. Regions such as the semi-arid Northeast and Vale do Jequitinhonha in Minas Gerais State historically face problems related to lack of water. In the last years the situation has worsened in terms of quantity and quality. Thus, the purpose of this study is to measure the quality of surface water in the basin of the Capivari river in the city of Chapada do Norte, Alto Jequitinhonha, northeast of Minas Gerais. It was used as analysis technique the Water Quality Index - WQI, used by the main agencies of the water management in Brazil, such as CETESB / SP and IGAM / MG. Key Words: sub-basin of Capivari river; Chapada do Norte; WQI. Palavras-Chave: Sub-bacia do rio Capivari; Chapada do Norte; IQA. Abstract: Water is one of the most precious natural resources and is indispensable to the maintenance of life. Knowing the quantity and quality of water resources of the country is a precondition for developing strategies that seek their conservation, recovery and rational use and indispensable goal for the whole society. It is known that the occupation and land use modify the physical, chemical and biological water resources. Despite being the country's most well apportioned in freshwater percentage terms, their geographical distribution is quite irregular in Brazil. Regions such as the semi-arid Northeast and Vale do Jequitinhonha in Minas Gerais State historically face problems related to lack of water. In the last years the situation has worsened in terms of quantity and quality. Thus, the purpose of this study is to measure the quality of surface water in the basin of the Capivari river in the city of Chapada do Norte, Alto Jequitinhonha, northeast of Minas Gerais. It was used as analysis technique the Water Quality Index - WQI, used by the main agencies of the water management in Brazil, such as CETESB / SP and IGAM / MG. Key Words: sub-basin of Capivari river; Chapada do Norte; WQI.